Desenvolvimento de sensores nanoestruturados para análise de realçadores de sabor em água - Fukushima, Katia Lumi (2017)
The objective of this work to develop, characterize and apply nanostructured sensors for the analysis of water flavor enhancers. For then, the gold interdigitaded electrodes were made on glass substrate and were used for sensors elaboration. The modification of the electrode surface was done through films using the Layer by Layer technique. Different architectures with Copper Tetrasulfonate Phthalocyanine, PANI (in its conductive state), Reduced Graphene Oxide, PAH and silver nanoparticles were used. The characterization of the sensors was done using the techniques of characterization with UV-VIS Spectroscopy and the evaluation of the electrical properties. The characterization of the solutions was done using FTIR, Field Emission Scanning Electron Microscopy (FEG-SEM) and Zeta Potential. For the application in the electronic tongue, a data acquisition system was used which is formed by an array of sensorial units (sensors). The solutions with different concentrations of flavor enhancer (guanylate and inosinate) and NaCl, were placed on sensors measuring the Electrical Impedance, which is converted into resistance at 1 kHz. Data were analyzed using Principal Component Analysis (PCA). It is possible to observe that the films were formed, because of the interaction of negative and positive charges which were confirmed by the FTIR and Zeta Potential. The electrode array was efficient to the identification of flavor enhancers and sodium chloride in high and low concentrations, being possible to use as a tool for analysis in the food industry.